2024
DOI: 10.1021/jacs.3c11653
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Enabled Dearomative Trifluoromethoxylation of Indoles

Zhijie Deng,
Lingduan Meng,
Xiao Bing
et al.

Abstract: The only known method for the dearomative trifluoromethoxylation of indoles is preliminary, with only one substrate successfully undergoing the reaction. In this study, we not only developed a broadly applicable method for indole dearomative trifluoromethoxylation but also achieved divergent trifluoromethoxylation by fine-tuning the reaction conditions. Under optimized conditions, with a silver salt and an easily handled OCF3 reagent, various indoles smoothly underwent dearomatization to afford a diverse array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…[18f] Very recently, they disclosed another new discovery in dearomative trifluoromethoxylation of indoles with TFMS (Scheme 9). [36] By fine-tuning the reaction conditions, divergent dearomative trifluoromethoxylation of indoles 9.1 was achieved for the preparation the ditrifluoromethoxylated indolines 9.4 in up to 37 : 1 diastereoselctivity as well as fluorinated trifluoromethoxylated indoles 9.5 in trans selectivity exclusively in the presence of silver difluoride salt. Furthermore, other types of heteroaromatic rings (such as benzothiazoles and benzofurans) and styrene derivatives were also compatible in the ditrifluoromethoxylation reactions.…”
Section: Trifluoromethoxylating (Ocf 3 ) Reagentsmentioning
confidence: 99%
“…[18f] Very recently, they disclosed another new discovery in dearomative trifluoromethoxylation of indoles with TFMS (Scheme 9). [36] By fine-tuning the reaction conditions, divergent dearomative trifluoromethoxylation of indoles 9.1 was achieved for the preparation the ditrifluoromethoxylated indolines 9.4 in up to 37 : 1 diastereoselctivity as well as fluorinated trifluoromethoxylated indoles 9.5 in trans selectivity exclusively in the presence of silver difluoride salt. Furthermore, other types of heteroaromatic rings (such as benzothiazoles and benzofurans) and styrene derivatives were also compatible in the ditrifluoromethoxylation reactions.…”
Section: Trifluoromethoxylating (Ocf 3 ) Reagentsmentioning
confidence: 99%
“…Despite these intriguing properties, methods for the direct introduction of the CF 3 O group remain underdeveloped. In this respect, in the past ten years, a few nucleophilic trifluoromethoxylating reagents as well as trifluoromethoxy radical precursors have been reported, significantly expanding the arsenal of the trifluoromethoxylating methodologies. , …”
mentioning
confidence: 99%
“…Generating NO 3 • from a high-valent Ag­(II) nitrate complex would lower the native redox potential from the anion and is also an effective method to tune the radical reactivity as well as increase the concentration of NO 3 • owing to the formation of a radical pool . The high-valent Ag­(II) nitrate itself might also actively participate in a bimolecular homolytic substitution (S H 2) pathway, contributing to the C–O bond formation in nitrooxylation …”
mentioning
confidence: 99%
“…Decarboxylative nitrooxylation with silver­(II) species 40 as a catalyst yielded similar results as the reactions where the active catalyst was prepared in situ from silver­(I) and oxidant (Figure B-2). The silver­(II)–nitrate complex has proven to be a versatile nitrate source for C–O bond formation, as a 28% yield of the product was obtained by reacting 40 with a thermally generated alkyl radical from 41a (Figure B-3). All these data confirmed that the high-valent silver­(II) nitrate complex is a versatile NO 3 resource pool, enabling facile C–O bond formation.…”
mentioning
confidence: 99%